PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KOMPUTER PADA MATA KULIAH PASTRY DI JURUSAN ILMU KESEJAHTERAAN KELUARGA FAKULTAS PARIWISATA DAN PERHOTELAN UNIVERSITAS NEGERI PADANG - Adelina, Julia; Baidar, Baidar; Elida, Elida (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
The aims of this study was to develop a computer-based learning media is valid and practical course on pastry in the ca of IKK FPP UNP. This study uses Research And Development (R & D) is the method used to produce a specific product and test the feasibility of the product. Products produced in the form of computer-based learning media in the Department of IKK FPP UNP. Data collection techniques in this study conducted using questionnaires given to lecturers caterers and questionnaire responses of students to the media developed and analyzed using analysis deskripstif which includes analysis of the validity, and analysis of the practicalities. The results of this study indicate that the validity of computer-based learning media on valid category (0.89). While the practicalities of the test, the lecturer / practitioner gives very practical category (92.7%) and students leave with a very practical category (88.7%). Based on these findings it can be concluded that computer-based learning media is valid and practical to be used as a medium of learning in the subject of Pastry.keywords : development, computer-based learning media, pastry